HADITS ABOUT EDUCATION CURRICULUM - Anri Naldi (Proceeding International Seminar of Islamic Studies, 2021)
Hadiths are communications, stories, conversations from the Prophet Muhammad which are found in many contexts both religion, world, history and events that occur which are explanations of the Koran which are also used as a source of law after the Koran. Other names that are often expressed for hadith are sunnah, khabar, and atsar. The curriculum is the path to salvation, glory and goodness. In Islam the curriculum used to be safe in the World and in the Hereafter is the Koran and Hadith, in education to carry out and run well and achieve the goals achieved must follow the educational curriculum. Hadiths about the educational curriculum are concepts made by Islamic education experts in order to integrate Islamic education into hadith science. The hadiths about curriculum are materials or lessons that are taught in education. The hadiths about this curriculum were compiled based on the educational curriculum taught by the Prophet Muhammad when in Mecca before the hijjrah and Medina after the hijjrah, the Prophet's curriculum at that time was Education of Tawheed / Faith, Worship Education, Moral Education, Physical Education and Reading and Writing Education.Keywords: Hadith, Curriculum, Education